GAMBARAN DEPRESI POSTPARTUM DI RSKIA SADEWA - Diniyah, Kharisah (Universitas Jenderal Achmad Yani Yogyakarta, 2017)
Background: The incidence of postpartum depression develops during pregnancy or after delivery with a prevalence of 10-15% incidence in developed countries and about 20% -40% in developing countries. Objective: The purpose of this study was to know the description of the incidence of postpartum depression in RS KiA Sadewa Methods: The type of this study was cross sectional with postpartum maternal population in 2 weeks postpartum with the number of 78 respondents. The inclusion criteria of postpartum maternal and postnatal cesarean delivery, postpartum visit and / or infant immunization examination in otpatient Rs KIA Sadewa , and willing to be the respondent by signing the informed concent sheet. The preceding criteria for previous depression, delivery of twins, and complications in the mother and / or infant (preeclampsia / eclampsia, postpartum infections, BB <2500 g) would increase the risk of postpartum depression. Result: The picture of postpartum depression in KIA Sadewa Hospital based on age in respondents <20 years and age 20-35 years found 3 respondents at risk of postpartum depression, based on education on respondents with low education there are 4 respondents at risk of experiencing postpartum depression. Primiparous mother got 5 (11,9%) respondents risked experiencing of postpartum depression, with type of vaginal delivery as many as 4 (11,1%) respondent at risk of postpartum depression Conclussion: Based on the results of this study concluded that postpartum KIA Sadewa women at risk of experiencing postpartum depression, so that early detection and counseling related penatalksanaan postpartum depression. Key word : Depression, postpartum